2023
DOI: 10.1007/s11858-023-01527-x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher noticing in mathematics education: a review of recent developments

Jonas Weyers,
Johannes König,
Thorsten Scheiner
et al.

Abstract: The teacher noticing construct is widely recognized in teacher competence and education research, particularly in the field of mathematics education. This paper surveys recent research on mathematics teacher noticing published between July 2019 and 2022, following an earlier literature review on teacher noticing across different disciplines. The study presented here analyzed 118 English-language articles published in peer-reviewed journals, focusing on conceptualizations, research methods, and relationships wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…In addition, Jacobs et al (2011) identified "deciding how to respond based on students' understanding" as the third component of teachers' attention and referred to it as "decision making." Currently, there is a growing body of research on teacher noticing (Weyers et al, 2023a) that focuses mostly on conceptualizations (e.g., Choy & Dindyal, 2021;Kaiser et al, 2017), intervention methods (e.g., Weyers et al, 2023b), and relationships with other constructs (e.g., Depaepe et al, 2020;Kaiser et al, 2015;Krauss et al, 2020), including teacher knowledge and beliefs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Jacobs et al (2011) identified "deciding how to respond based on students' understanding" as the third component of teachers' attention and referred to it as "decision making." Currently, there is a growing body of research on teacher noticing (Weyers et al, 2023a) that focuses mostly on conceptualizations (e.g., Choy & Dindyal, 2021;Kaiser et al, 2017), intervention methods (e.g., Weyers et al, 2023b), and relationships with other constructs (e.g., Depaepe et al, 2020;Kaiser et al, 2015;Krauss et al, 2020), including teacher knowledge and beliefs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their survey paper for the 2019-2022 research literature on teacher noticing in mathematics education, Weyers et al (2023) concluded about the dominance of psychologicalcognitive orientations and the pervasiveness of the focus on students' mathematical thinking. These authors also concluded about the increasing diversification of foci and theoretical orientations in the literature surveyed, including social and sociocultural orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Making sense of students' ideas is also a critical part of noticing students' thinking, which has attracted much attention in teacher education research over the past two decades (for overviews, see Dindyal et al, 2021;Kaiser et al, 2023;König et al, 2022;Scheiner, 2016;Stahnke et al, 2016;Weyers et al, 2024). Although teacher noticing is arguably embodied, cultural and positional in important ways (Scheiner, 2021), much of the research on teacher noticing has understood noticing as being composed of two psychological processes: paying attention to and making sense of students' thinking (Sherin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%